Influence of process-induced shrinkage and annealing on the thermomechanical behavior of glass fiber-reinforced polypropylene. (20th January 2019) - Mulle, M.; Wafai, H.; Yudhanto, A.; Lubineau, G.; Yaldiz, R.; Schijve, W.; Verghese, N.
Abstract: We investigate the influence of process-induced shrinkage and subsequent annealing on the thermomechanical behavior of unidirectional laminates made of continuous glass fiber-reinforced polypropylene (GFPP). We use two different industrial lamination processes: static hot-press (SHP), and double-belt press (DBP) that are characterized by different cooling rates and pressure levels and most importantly, by the use of a closed mold in the case of SHP manufacturing. We measure the longitudinal and transverse shrinkage during the manufacturing and annealing processes using embedded fiber Bragg gratings (FBGs). The SHP molding reveals much lower induced shrinkage in GFPP as compared to the DBP process, although the relatively slow cooling should promote a higher degree of crystallization. We ascribe this to the constraining effect of the metallic mold used with the SHP process. The poor thermal conductivity of the mold is also responsible for a layer-like crystal microstructure in the GFPP matrix, causing a specific relaxation effect during the post-process heating treatment. Annealing generates additional shrinkage that is due to an increased degree of crystallinity and to the partial relaxation of residual stresses. However, the thermal expansion properties remain impacted by the process-induced strain state of the GFPP laminates and are still process-dependent after annealing.